THE EFFECT OF CAPITAL EXPENDITURE ON RETURN ON EQUITY: DUPONT APPROACH ANALYSIS - Krismonika Hidayat; Yossinomita Yossinomita; La Chica Salsabila Bilqis (JURNAL STUDI MANAJEMEN ORGANISASI, 2026)
This study examines the effect of CapEx on ROE using the DuPont Analysis framework and investigates the mediating roles of NPM, TAT and EM in this relationship. The study employs a quantitative approach using panel data from seven companies over the 2020-2024 period, yielding 35 observations. Data are analyzed using panel data regression with Fixed Effect and Random Effect Models, while mediation effects are assessed using the Sobel test. The findings reveal that Capital Expenditure does not have a direct significant effect on ROE. However, Capital Expenditure has a significant effect on Net Profit Margin, while its effect on Total Asset Turnover and Equity Multiplier is not significant. Mediation analysis indicates that Net Profit Margin significantly mediates the relationship between Capital Expenditure and ROE. In contrast, Total Asset Turnover shows limited mediating evidence, and Equity Multiplier does not mediate the relationship. These results suggest that the impact of Capital Expenditure on financial performance primarily operates through profitability rather than asset efficiency or leverage structure. This study contributes by clarifying the transmission mechanism of investment decisions to shareholder returns within the DuPont framework and provides practical implications for corporate managers in optimizing capital allocation decisions.